Texture-Based Analysis of 100 MR Examinations of Head and Neck Tumors – Is It Possible to Discriminate Between Benign and Malignant Masses in a Multicenter Trial? - Fruehwald-Pallamar, J.; Hesselink, J. R.; Mafee, M. F.; Holzer-Fruehwald, L.; Czerny, C.; Mayerhoefer, M. E. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2016)
Aim: To evaluate whether texture-based analysis of standard MRI sequences can help in the discrimination between benign and malignant head and neck tumors.Materials and Methods: The MR images of 100 patients with a histologically clarified head or neck mass, from two different institutions, were analyzed. Texture-based analysis was performed using texture analysis software, with region of interest measurements for 2 D and 3 D evaluation independently for all axial sequences. COC, RUN, GRA, ARM, and WAV features were calculated for all ROIs. 10 texture feature subsets were used for a linear discriminant analysis, in combination with k-nearest-neighbor classification. Benign and malignant tumors were compared with regard to texture-based values.Results: There were differences in the images from different field-strength scanners, as well as from different vendors. For the differentiation of benign and malignant tumors, we found differences on STIR and T2-weighted images for 2 D, and on contrast-enhanced T1-TSE with fat saturation for 3 D evaluation. In a separate analysis of the subgroups 1.5 and 3 Tesla, more discriminating features were found.Conclusion: Texture-based analysis is a useful tool in the discrimination of benign and malignant tumors when performed on one scanner with the same protocol. We cannot recommend this technique for the use of multicenter studies with clinical data.Key Points:Citation Format:• Fruehwald-Pallamar J., Hesselink J. R., Mafee M. F. et al. Texture-Based Analysis of 100 MR Examinations of Head and Neck Tumors – Is It Possible to Discriminate Between Benign and Malignant Masses in a Multicenter Trial?. Fortschr Röntgenstr 2016; 188: 195 – 202
Keywords: head/neck; tissue characterization; MR imaging; technology assessment